The Effectiveness of Ice Breaking to Increase Students’ Motivation in Learning English - adi, mohammad sofyan; Susanti, Riska Ayu; Jannah, Qomariatul (Universitas Nurul Jadid, 2021)
This study was generally attempted to find the effect of ice breaking to increase students' motivation in English learning at the first grade of SMP Nurul Jadid. This research used pre-experimental design by using one shot case study pre-test and post-test. Before the treatment, the researcher gave the pre-test in one class. Moreover, the researcher taught English by using ice breaking in the experimental class. The last, the researcher conducted the post-test to know whether an ice breaking was effective for teaching English in experimental class. Based on the data analysis, the data t-test (2.77) was higher than t-table value (2.042). The result analyzing showed that there was significant difference on the students’ motivation taught by using ice breaker. The students’ mean score of the pre-test of the experiment class was 60. Then, in the post-test, the mean score of experiment class was 66.1. Therefore, hypothesis H0 was rejected and H1 was accepted. It concluded that ice breaking was effective in teaching English learning toward the students’ motivation for the first grade of SMP Nurul Jadid. Thus, this research make students be enjoy, be active, energize, feeling happiness, interactive in the classroom, stay in the class during learning process, and focus on the material.